2017
DOI: 10.4049/jimmunol.1502181
|View full text |Cite
|
Sign up to set email alerts
|

Host-Derived CD70 Suppresses Murine Graft-versus-Host Disease by Limiting Donor T Cell Expansion and Effector Function

Abstract: Allogeneic hematopoietic cell transplantation (allo-HCT) is a potentially curative treatment for hematologic and immunologic diseases. However, graft-versus-host disease (GVHD) may develop when donor-derived T cells recognize and damage genetically distinct normal host tissues. In addition to T cell receptor signaling, co-stimulatory pathways are involved in T cell activation. CD27 is a TNF receptor family member expressed on T cells and its ligand, CD70, is expressed on APCs. The CD27/CD70 co-stimulatory path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…Meanwhile, we have confirmed this immune inhibitory function in both IBD and allogeneic GVHD models. Furthermore our recent publication shows that host-derived CD70 suppresses GVHD by limiting donor T cell expansion and effector function (34). Together our studies have demonstrated that T cell intrinsic CD70 signaling as well as CD27–CD70 interaction in both donor T cells and the host immune cells may contribute to the suppression of inflammatory T cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, we have confirmed this immune inhibitory function in both IBD and allogeneic GVHD models. Furthermore our recent publication shows that host-derived CD70 suppresses GVHD by limiting donor T cell expansion and effector function (34). Together our studies have demonstrated that T cell intrinsic CD70 signaling as well as CD27–CD70 interaction in both donor T cells and the host immune cells may contribute to the suppression of inflammatory T cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…CD27 + and CD70 + cells often secrete higher levels of IFNɣ and are therefore more effective at inhibiting viral replication [220]. This is in contrast to studies looking at CD27 in the context of strong and persistent immune challenges, such as chronic infections or GVHD, where CD27-CD70 have been shown to play an inhibitory role on T cell responses [216,[223][224][225]. The role of CD27 in diseases is also dependent on tissue context and duration of expression [22].…”
Section: Cd27 and Cd70mentioning
confidence: 99%
“…The clinical GVHD manifestations are weight loss; change in posture, activity, fur texture, hair loss and in some cases diarrhea. Clinical GVHD is evaluated comprehensively with a scoring system as published before (17, 20).…”
Section: Methodsmentioning
confidence: 99%